Student Professional Development: Fostering Critical Thinking among Students - Mishra, B. K.; Jolly, Lochan; Bahuguna, Rajni (Journal of Engineering Education Transformations, 2025)
Student Professional Development is defined as the activities that enable to supplement and complement the curricular or main syllabi activities. These are the very important part and parcel of educational institutions to develop the students‟ personality as well as to strengthen the classroom learning directly or indirectly. Professional development (PD) can be defined in diverse ways and can take many forms. Formal education is classroom education, with nonformal considered as “any organized, systematic, educational activity, carried on outside the framework of the formal system, to provide selected types of learning to a particular subgroup in the population. A problem higher education faculty face is the lack of a framework for holistic student professional development and assessment. Such a framework can serve as a bridge between academic and professional identity development This article presents the framework planned in the institute for professional development of students where the students learn by Informal education by association and affiliation, specifically, “the life-long process by which every person acquires and accumulates knowledge, skills, attitudes, and insights from daily experiences and exposure to the environment. The idea is to facilitate an academic mixed with co-curricular and extra co-curricular culture so that they can participate as effectively . Our mixed-methods study examined the impact of many activities leadership, classroom experiences, and sociocultural levels; the findings inspire new directions for program design with key insights for student PD program evaluation.